Munir, Walid. “Sufism and the Psychology of Transcendent Presence: Between Motivation and Purpose,” Year 9, Issue 36 (Spring 1425 AH/ 2004 CE), Pp. 123-158. - منير وليد (Al-Fikr al-islāmī al-muʿāṣir (previously Islamiyat al-Ma’rifah), 2004)
Walid Munir’s article is an exploratory study aimed at learning the psychological phenomenon of Sufism (including mysticism) in its deep concepts and methods of practice, based on philosophical and reflective psychology. Munir asserts that the approach adopted in his study provides a measure of objectivity. His article discusses the psychological dimension in the concept of Sufism among Sufis, the foundation (ta’ṣīl) of the psychological dimension in the concept of Sufism from the reality of the Qur’an and Sunnah, the characteristics of a Sufi character, and psychological motives to Sufism and the loss of a sense of harmony. Munir calls for continued research into the subject, based on a clear methodological objective, and establishes a framework for what is referred to as “religious psychology.”